Spore liberation in mosses revisited. Issue 1 (23rd December 2017) - Gallenmüller, Friederike; Langer, Max; Poppinga, Simon; Kassemeyer, Hanns-Heinz; Speck, Thomas
Abstract : Gallenmüller et al. provide an analysis of spore liberation in mosses in response to humidity conditions. The study presents, for the first time, temporally and spatially well-resolved kinematic analyses of the complex hygroscopic movements performed by the peristome teeth inserted at the mouth of the spore capsule and gives insights into their sophisticated functional morphology and anatomy. The authors explain these movements by relating gradients in the composition of the peristome teeth to differences in swelling capacity and velocity between the tip and the base of the teeth and also between different teeth layers. Abstract: The ability to perform hygroscopic movements has evolved in many plant lineages and relates to a multitude of different functions such as seed burial, flower protection or regulation of diaspore release. In most mosses, spore release is controlled by hygroscopic movements of the peristome teeth and also of the spore capsule. Our study presents, for the first time, temporally and spatially well-resolved kinematic analyses of these complex shape changes in response to humidity conditions and provides insights into the sophisticated functional morphology and anatomy of the peristome teeth. In Brachythecium populeum the outer teeth of the peristome perform particularly complex hygroscopic movements during hydration and desiccation. Hydration induces fast inward dipping followed by partial re-straightening of the teeth. In their final shape, wet teeth close the capsule. During desiccation, the teeth perform an outward flicking followed by a re-straightening which opens the capsule. We present a kinematic analysis of these shape changes and of the underlying functional anatomy of the teeth. These teeth are shown to be composed of two layers which show longitudinal gradients in their material composition, structure and geometry. We hypothesize that these gradients result in (i) differences in swelling/shrinking capacity and velocity between the two layers composing the teeth, and in (ii) a gradient of velocity of swelling and shrinking from the tip to the base of the teeth. We propose these processes explain the observed movements regulating capsule opening or closing. This hypothesis is corroborated by experiments with isolated layers of peristome teeth. During hydration and desiccation, changes to the shape and mass of the whole spore capsule accompany the opening and closing. Results are discussed in relation to their significance for humidity-based regulation of spore release.